Cosmeceutical product consisting of biomimetic peptides: antiaging effects in vivo and in vitro - Gazitaeva ZI; Drobintseva AO; Chung Y; Polyakova VO; Kvetnoy IM (Dove Medical Press, 2017)
Zarema I Gazitaeva,1 Anna O Drobintseva,2 Yongji Chung,3 Victoria O Polyakova,2 Igor M Kvetnoy2 1Institute of Beauty Fijie, Moscow, 2Department of Pathomorphology, D.O. Ott Research Institute of Obstetrics, Gynecology and Reproductology, Saint-Petersburg, Russian Federation; 3Caregen Co., Ltd. Research Center, Seoul, South Korea Background: Biomimetic peptides are synthetic compounds that are identical to amino acid sequence synthesized by an organism and can interact with growth factor receptors and provide antiaging clinical effects.Purpose: The purpose of this study was to investigate the effects of biomimetic peptides on the repair processes in the dermis using a model of cell cultures and in vivo.Patients and methods: Five female volunteers were subjected to the injection of biomimetic peptides 1 month prior to the abdominoplasty procedure. Cell culture, immunocytochemistry, and confocal microscopy methods were used in this study.Results: Biomimetic peptides regulate the synthesis of proteins Ki-67, type I procollagen, AP-1, and SIRT6 in cell cultures of human fibroblasts. They contribute to the activation of regeneration processes and initiation of mechanisms that prevent aging. Intradermal administration of complex of biomimetic peptides produces a more dense arrangement of collagen fibers in the dermis and increased size of the fibers after 2 weeks. The complex of biomimetic peptides was effective in the in vivo experiments, where an increase in the proliferative and synthetic activities of fibroblasts was observed.Conclusion: This investigation showed that the studied peptides have biological effects, testifying the stimulation of reparative processes in the skin under their control. Keywords: biomimetic peptides, skin aging, collagen, reparation processes, mesotherapy